ANALYSIS OF THE NON-DISCRIMINATORY PRINCIPLE IN THE PROTECTION OF HUMAN RIGHTS AGAINST REFUGEES IN GLOBAL CONFLICT AREAS - Muh. Syah Quddus Quddus; Arika Dwi Astuti; Masrifah Nufitasari (Sociale : Journal of Social and Political Sciences, 2025)
The protection of human rights for refugees in global conflict zones has become a crucial issue requiring greater attention, as many host countries implement selective policies based on political or economic interests. Although the principle of non-discrimination is established in international law, discriminatory practices against refugees based on geographic origin or religion frequently occur, particularly in Europe. This study aims to analyze the implementation of the non-discrimination principle in human rights protection for refugees and to identify gaps in its application at both international and national levels. The research employs a normative juridical approach by analyzing secondary data from primary, secondary, and tertiary legal materials. The findings indicate that non-discriminatory protection for refugees continues to face significant challenges despite the existing international legal framework, as host countries often fail to effectively implement this principle. Domestic legal reforms, strengthened monitoring mechanisms, and multilateral collaboration are necessary to establish a more equitable and just refugee protection system. International organizations such as UNHCR and IOM play a key role in ensuring the implementation of the non-discrimination principle through stricter oversight of host country policies and training for relevant authorities.